Burton Dassett Southend, Warwickshire. A Medieval Market Village - Rogerson, Andrew (Medieval Settlement Research, 2023)
30 years’ delay preceded publication of this very significant volume, but it was worth the wait. Non-stop excavation between May 1986 and September 1988 took full advantage of an abundant workforce supplied by the Manpower Services Commission and the landowner’s generosity in permitting sufficient time before construction of the M40 Oxford-to-Birmingham motorway extension, with results more closely resembling those of a research rather than a rescue project.